Use of Liquid Phenol for Management of Pilonidal Disease - Alaattin Öztürk; Yüksel Karaköse (İstanbul Medical Journal, 2019)

(untitled)
Introduction:This study describes the treatment of pilonidal sinus with liquid phenol and reports its short-term results.Methods:Patients with pilonidal disease were operated under local anesthesia. Primary and secondary pits were excised. Pilonidal cyst cavity was cleaned with brushing, curettage and irrigation. Wounds were left open. Chemical destruction of sinus wall was performed by liquid phenol.Results:A total of 67 patients with pilonidal sinus were enrolled in this study. The mean duration of surgery was 14.7 minutes. The mean follow-up period was 27.3 months. There were no systemic complications. Two patients had hemorrhage and three patients had wound infection. The wound healing time was 3-6 weeks. Three cases of recurrence were observed in the follow-up period (4.47 %).Conclusion:Minimally-invasive surgical technique with liquid phenol is a safe and effective outpatient procedure that can be performed under local anesthesia. It has low recurrence and postoperative morbidity rates.